Role of Neuroprotective Agents in the Anesthetic Management of Brain Tumors for Patients with Recidive Cystic Tumor with Signs of Intracranial Hypertension Underwent Re-Craniotomy Decompression Tumor Resection: Case Report - Utami, Yulia Kartika; Prihatno, Rudi; Suryani, Shila (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: The management of brain tumor surgeries, particularly recurrent cystic tumors with cerebral edema, poses significant challenges. Elevated intracranial pressure (ICP) and the associated risk of ischemia necessitate a comprehensive neuroprotective approach during anesthesia to ensure optimal surgical and postoperative outcomes.Case: A 54-year-old male presented with two weeks history of headaches and dizziness. He had previously undergone a craniotomy six months ago for the removal of a metastatic right parieto-occipital adenocarcinoma. Imaging revealed tumor recurrence, and the patient was scheduled for a re-craniotomy. The anesthetic plan included neuroprotective strategies: thiopental for metabolic suppression, sufentanil for hemodynamic stability, and sevoflurane for neuroprotection. The surgery lasted 3.5 hours, with minimal intraoperative blood loss and stable perioperative hemodynamics. Postoperatively, the patient recovered without complications and was discharged in stable condition.Discussion: The anesthetic management prioritized maintaining ICP, cerebral perfusion pressure (CPP), and minimizing neuroinflammatory responses. Thiopental effectively reduced cerebral metabolic demands, sufentanil stabilized hemodynamics, and sevoflurane provided neuroprotective and anti-inflammatory benefits. hypothesis and principles. These strategies ensured cerebral autoregulation, controlled cerebral edema, and optimized recovery. The Monro-Kellie hypothesis and principles of neuroprotection were key guiding frameworks in this case.Conclusion: This case highlights the critical role of neuroprotective agents in the anesthetic management of brain tumor surgeries. The combination of thiopental, sufentanil, and sevoflurane contributed to a stable intraoperative course and uneventful recovery. Integrating these strategies ensures improved surgical outcomes and patient safety in challenging neurosurgical cases.